Thief of fate [large type] - Deveraux, Jude; Sheets, Tara, 1973- (Deveraux, Jude. Providence Falls, 2022)
"When Liam O'Connor stole Cora McLeod from her destined soul mate, Finley Walsh, in 1844, he changed the course of history. Now Liam has been given three months to set things right, but he has failed to reunite Cora and Finn. And with time running out, things are looking worse than ever. As the three investigate a murder case together, they are caught in a devilish love triangle. Finn has always loved Cora. She has finally realized she wants Liam. And Liam knows he has no choice but to push Cora away if he has any hope of avoiding eternal damnation. The angels have made it clear-balance must be restored. As Liam tries desperately to make amends, he realizes his actions in the past have put them all in grave danger. And, once again, someone will pay the ultimate price"--